Energy Demand and Financial Sector Performance in Sub-Saharan African Region - Wakeel, Isola; Bello, Ajide Kazeem (International Journal of Sustainable Energy and Environmental Research, 2014)
This study analyzed the impact of energy demand on financial sector performance in Sub Saharan African. It adopted the production theory that was augmented with energy input. The study considered a panel unit root and co-integration test to examine the time series properties of the variables and a static panel estimation technique (pooled, fixed and random effect model) to determine the impact of production inputs on financial sector performance in SSA. The result reveals that energy demand weakens financial sector performance (showing a negative relationship), but when interacted with labour force it strengthens financial sector performance in SSA. The study, thus, attributed the negative relationship between energy demand and financial sector performance to the externalities produced from energy usage. This study therefore recommends that to support the growth of the financial sector, gross capital formation should be intensified and efficiently used and also that energy use should be effectively combined with labour force to strengthen the financial sector.